Resveratrol Prevents Cellular and Behavioral Sensory Alterations in the Animal Model of Autism Induced by Valproic Acid - Fontes-Dutra, Mellanie; Santos-Terra, Júlio; Deckmann, Iohanna; Brum Schwingel, Gustavo; Della-Flora Nunes, Gustavo; Hirsch, Mauro Mozael; Bauer-Negrini, Guilherme; Riesgo, Rudimar S.; Bambini-Júnior, Victorio; Hedin-Pereira, Cecília; Gottfried, Carmem (Frontiers in Synaptic Neuroscience, 2018)
Autism spectrum disorder (ASD) is characterized by impairments in both social communication and interaction and repetitive or stereotyped behaviors. Although its etiology remains unknown, genetic and environmental risk factors have been associated with this disorder, including the exposure to valproic acid (VPA) during pregnancy. Resveratrol (RSV) is an anti-inflammatory and antioxidant molecule known to prevent social impairments in the VPA animal model of autism. This study aimed to analyze the effects of prenatal exposure to VPA, as well as possible preventive effects of RSV, on sensory behavior, the localization of GABAergic parvalbumin (PV+) neurons in sensory brain regions and the expression of proteins of excitatory and inhibitory synapses. Pregnant rats were treated daily with RSV (3.6 mg/kg) from E6.5 to E18.5 and injected with VPA (600 mg/kg) in the E12.5. Male pups were analyzed in nest seeking behavior and in whisker nuisance task. At P30, the tissues were removed and analyzed by immunofluorescence and western blotting. Our data showed for the first time an altered localization of PV+-neurons in primary sensory cortex and amygdala. We also showed a reduced level of gephyrin in the primary somatosensory area of VPA animals. The treatment with RSV prevented all the aforementioned alterations triggered by VPA. Our data shed light on the relevance of sensory component in ASD and highlights the interplay between RSV and VPA animal model as an important tool to investigate the pathophysiology of ASD.